FAKTOR – FAKTOR YANG MEMPENGARUHI KELENGKAPAN LAPORAN KEUANGAN - Moh. Halim* Vicky Sampurno** (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2015)
User of financial statements is an important thing for the user informasi. The aim in this study was to analyze the factors affecting the level of completeness of the disclosure of financial statements at companies listed on the Indonesian Stock Exchange (BEI) . Population in this research are manufacturing companies listed on the Stock Exchange the period of 2012-2014 . Samples taken by using purposive sampling judgment and obtained 179 Integration for 3 years . Techniques of analysis using multiple linear regression analysis . So getting the results of research that shows that laverage ( DER ) , liquidity ( CR ) , profitability ( ROA ) , Public Shares and Age no positive effect on the completeness of the financial statements .